The Moderating Role of Brand Love and Brand Obsess in Customer-Oriented Deviance: An Exploratory Study - Abbas, Zaki Muhammad; Jasim, Saif Ali; Idan, Afrah Raheem (International Journal of Economics, Management and Accounting, 2025)
The current research examines the interactive role of brand love in its dimensions (brand passion, brand familiarity, brand commitment) and obsession with brand in the customer-oriented deviation represented in (financial motives, ego motives, motives of revenge), and accordingly, the opinions of some customers towards some tourism and travel companies have been surveyed by five companies (Bright Light Company for Tourism and Travel, and Al-Mohib Company for Tourism and Travel,  And the Banner Summit Company for Travel and Tourism, Al-Shams International Company, and Icor Company) for the period (June to late August 2024) and customers showed great cooperation by responding to the paragraphs of the study tool, Accordingly, (593) opinions were collected from the opinions of customers dealing with these companies, and the descriptive analytical approach was adopted in building and interpreting the study variables through the use of statistical packages for the program (SPSS&AMOS). V.28) The results presented that the interactive role of brand love and obsession with tourism companies is closely related to addressing customer-oriented deviation and this motivated these companies to develop their capabilities by providing comfort, air conditioning and distinctive services, but in theory the research has shown a conceptual relationship between brand love and obsession with customer-oriented deviation through what was presented by some previous studies.